Phytochemical constituents of Hymenophyllum javanicum spreng., Huperzia carinata (Desv. ex Poir.) Trevis and Huperzia nummolarifolia (Blume) Jermy - Mohd Rani, Hazwani (2015)
Huperzia carinata and Huperzia nummolarifolia were chosen to be studied along with Hymenophyllum javanicum due to their relation in their phylogeny. These plants have been used traditionally for the treatment of contusions, strains, swellings, schizophrenia, myasthenia gravis and organophosphate poisoning. The purpose of this study is to isolate and purify the chemical constituents for these species and elucidate the structures of the compounds isolated. The isolation procedures were carried out by using a few separation methods such as column chromatography, Sephadex and SPE. As a result, four compounds have been isolated from both Huperzia species. They are 14β,21α-dihydroxyserrat-3β-yl acetate (S4), 14β,21β- dihydroxyserrat-3β-yl acetate (S6), serratenediol (N2211-1-4) and 14β,21β- trihydroxyserrat-3β-yl-p-dihydrocaffeate (E377). Whereas, four compounds have been isolated from Hymenophyllum javanicum which are, Hymenoside W (KS-5), [6-(3,4-dihydroxy-2-methylenebutoxy)-3,4,5-trihydroxytetrahydro-2H-pyran-2- yl)methyl-2-(3,4 dihydroxyphenyl)acetate] (KS-10-2) [6-(3,4-dihydroxy-2- methylenebutoxy)-2-{[2-(3,4-dihydroxyphenyl)acetoxy]methyl}-4,5-dihydroxytetrahydro- 2H-pyran-3-yl-2-phenylacetate] (KS-8-10-4) and [6-(3,4-dihydroxy-2- methylenebutoxy)-5-hydroxy-2-{(2-phenylacetoxy)methyl}tetrahydro-2H-pyran- 3,4-diyl-bis{2-(3,4-dihydroxyphenyl)acetate}] (KS-8-10-6). The structures of isolated compounds were identified based on spectroscopic data including 1D and 2D NMR and comparison with the literature.